Equipment Leasing Model with Failure Tolerance Cost Using Game Theory - Bayu Nur Abdallah; Ahmad Jamil; Nani Kurniati (Institut Teknologi Sepuluh Nopember, 2020)
In this study the equipment lease contract, where two players, the lessor, lease the equipment to the user (lessee), if the equipment fails to exceed the tolerance agreed by both players during the lease period and needs to be repaired, it is considered detrimental to the lessee, because it results in a loss of potential revenue will be received from leased equipment. Therefore, the total income of the lessor in the lease contract may incur penalty costs as a consequence of the lessor for failure to maintain maintenance performance. We use Nash's game theory formulation to find a win-win solution between players where it is an equilibrium point for lessor and lessee. The results of this study are, when Lessee decides to maximize profits, which is the total potential profit gained by the lessee using leased equipment, and the lessor also decides to maximize their profits derived from the leased equipment by considering penalty cost as a cooperatively determined variable. The selected scenario is the percentage of the minimum penalty cost with the maximum level of equipment used.